Effect of deposition parameters on crystalline of CVD diamond. Issue 197 (24th March 2019) - Shouxin, Yu; Zhao, Zhang; Wenzhuang, Lu; Dunwen, Zuo
Abstract: CVD diamond films were prepared on the cemented carbide substrate by hot filament chemical vapor deposition method. The diamond coatings were observed with SEM and Raman spectroscopy. The results show that the increase of vaccum pressure greatly promotes the continuous increase of grain size, and the impurity content of diamond is decreasing with the increase of vaccum pressure. With the increase of the CH4 concentration, the grain size of diamond decreases continuously and the composition of non-diamond carbon increases, but when the CH4 is more than 3% the grain size does not change obviously. The substrate temperature has a certain influence on the structure and grain size of NCD. The multilayer NCD/MCD coated cutting tool was prepared by controlling the deposition parameters.